2015
DOI: 10.1590/0103-8478cr20150370
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of nematodes against larvae of the south-American fruit fly in laboratory using soil from Porto Amazonas, Paraná, Brazil, as substrate

Abstract: Anastrepha fraterculus is an important orchard pest. Its management has been based in chemical sprays

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…The incidence of EPNs inside dead Caribfly suggests that at least Caribfly larvae are hosts to EPNs. Observations in this study were similar to those reported on Ceratitis capitata , Anastrepha ludens , Anastrepha fraterculus and Bactrocera oleae among others . As shown here, larvae of Caribfly are the most susceptible soil‐inhabiting stage to virulent nematodes because Caribfly larvae are very active and highly motile compared with motionless and diapausing pupae which are noted for very low oxygen consumption .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The incidence of EPNs inside dead Caribfly suggests that at least Caribfly larvae are hosts to EPNs. Observations in this study were similar to those reported on Ceratitis capitata , Anastrepha ludens , Anastrepha fraterculus and Bactrocera oleae among others . As shown here, larvae of Caribfly are the most susceptible soil‐inhabiting stage to virulent nematodes because Caribfly larvae are very active and highly motile compared with motionless and diapausing pupae which are noted for very low oxygen consumption .…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the longest (or largest) steinernematids were more effective at suppressing emerging adults following inoculation of pupae in soil microcosms. Pupal mortalities due to EPN species in treatments were generally low and similar to those reported on Mexican fruit fly ( A. ludens ), olive fruit fly ( B. olae ) and Mediterranean fruit fly ( C. capitata ) among others in previous studies, suggesting that EPNs are not able to penetrate and infect pupae of fruit flies because of pupal resistance . Reports explained that the closure of all openings (e.g.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Rohde et al (2012) found mortality rates of C. capitata larvae higher than 90%. Similar results were found by Foelkel, Monteiro and Voss (2016) for Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae); by Heve et al (2017) for Anastrepha suspensa (Loew) (Diptera: Tephritidae); and by Sirjani, Lewis and Kaya (2009) for Bactrocera oleae (Gmelin) (Diptera: Tephritidae). Rohde et al (2012) tested the efficiency of S. carpocapsae ALL nematodes in controlling C. capitata pupae and found mortality rate of 20% when using 200 IJs per insect, equivalent to 100 IJs cm -2 .…”
Section: Entomopathogenic Nematode Concentration On Larvae and Pupae supporting
confidence: 80%
“…Studies have demonstrated that NEPs are effective in controlling pests of different crops (FOELKEL et al, 2016;GIOMETTI et al, 2011;MANACHINI et al, 2013). Feaster and Steinkraus (1996) and Andaló et al (2010) assessed pupae control of Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) and Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) in maize using NEPs; both pests had mortality rates higher than 90%.…”
Section: Introductionmentioning
confidence: 99%